2017
DOI: 10.1136/bmjopen-2017-016925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of national implementation of utstein recommendation from the global resuscitation alliance on ten steps to improve outcomes from Out-of-Hospital cardiac arrest: a ten-year observational study in Korea

Abstract: ObjectivesThe Utstein ten-step implementation strategy (UTIS) proposed by the Global Resuscitation Alliance, a bundle of community cardiopulmonary resuscitation (CPR) programs to improve outcomes after out-of-hospital cardiac arrests (OHCAs), has been developed. However, it is not documented whether UTIS programs are associated with better outcomes or not. The study aimed to test the association between the UTIS programme and better outcomes after OHCA.MethodsThe study was a before- and after-intervention stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 33 publications
(23 reference statements)
0
46
2
Order By: Relevance
“…Our ndings, although preliminary, showed that survival outcomes of OHCA patients in Daegu during the peak of the COVID-19 outbreak (4.1%) were signi cantly lower than those reported nationwide (9.8%) or in the city (8.8%) in 2018 [18]. We could not describe the broken chain of survivaland the negative effects on high-quality CPR in the results of the present study;however, due to this pandemic, the risk-bene t balance for CPRshould be reconsidered [2].Other studies have also raised the question of how CPRmust be performed for IHCA patients with con rmed COVID-19.Considering the lower survival rate, physicians should be concerned about the goals of care or CPR preferences to reduce futile resuscitation by stratifying survivability of the IHCA patients, regardless of their COVID-19 status, at the time of hospital admission [5,19].…”
Section: Discussioncontrasting
confidence: 70%
“…Our ndings, although preliminary, showed that survival outcomes of OHCA patients in Daegu during the peak of the COVID-19 outbreak (4.1%) were signi cantly lower than those reported nationwide (9.8%) or in the city (8.8%) in 2018 [18]. We could not describe the broken chain of survivaland the negative effects on high-quality CPR in the results of the present study;however, due to this pandemic, the risk-bene t balance for CPRshould be reconsidered [2].Other studies have also raised the question of how CPRmust be performed for IHCA patients with con rmed COVID-19.Considering the lower survival rate, physicians should be concerned about the goals of care or CPR preferences to reduce futile resuscitation by stratifying survivability of the IHCA patients, regardless of their COVID-19 status, at the time of hospital admission [5,19].…”
Section: Discussioncontrasting
confidence: 70%
“…Since 2008, we have enacted the Good Samaritan Law and maintained the mandated first responder and school CPR programs. Since 2011, the DACPR system has been operated by the national EMS [6]. erefore, the bystander CPR rate has increased dramatically, as seen in this study.…”
Section: Discussionmentioning
confidence: 62%
“…e elderly are generally physically weaker than younger people. In a 2008 study, the participants of a mandatory training program for CPR were students and first responders [6]. Retired elderly were likely to lack CPR knowledge because they had fewer educational opportunities.…”
Section: Factors Affecting Bystander Cpr Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…First aid is the assistance given to a person suffering from sudden illness or injury, to preserve life, prevent the condition from worsening, and reducing the severity of injuries (Helsloot and Ruitenberg, 2004). The 2015 International Liaison Committee on Resuscitation (ILCOR) Consensus on Science and Treatment Recommendations and reviews by Red Cross Red Crescent National Societies reported a signi icant increase in survival rates and reduced time to resolution of symptoms for ill or injured persons after a comprehensive irst aid training (Singletary et al, 2015;Kim et al, 2017). Children are more vulnerable to unintentional injuries due to the fact that they are less acquainted of themselves and environmental dangers.…”
Section: Introductionmentioning
confidence: 99%